2022-RA-1453-ESGO Chemotherapy response score as a predictor of survival among patients undergoing interval debulking surgery for ovarian cancer. (20th October 2022) - Rodolakis, Ioannis; Liontos, Michalis; Papadatou, Konstantina; Prodromidou, Anastasia; Haidopoulos, Dimitrios; Rodolakis, Alexandros; Bamias, Aristotelis; Thomakos, Nikolaos
Abstract : Introduction/Background: Neo-adjuvant chemotherapy has been adopted as an alternative mode of therapy for surgically irresectable ovarian cancer in cases of diffuse dissemination, where primary debulking surgery is not feasible or when patient status does not allow extensive procedures. The response to chemotherapy can be evaluated objectively with the use of standard pathology. In the present study we evaluated the prognostic significance of chemotherapy response score in predicting survival rates of patients undergoing interval debulking surgery. Methodology: The study is based in a retrospective cohort of patients. We collected data from 48 ovarian cancer patients that received at least 3 cycles of neo-adjuvant chemotherapy. The evaluation of chemotherapy response score was based on pathology sections of the omentum and ovaries. Following interval debulking surgery chemotherapy was continued until the completion of 6 cycles of perioperative treatment. Twenty two patients received maintenance therapy with bevacizumab following completion of chemotherapy. Results: Median follow-up was 52.5 months ranging between 38.5 and 70.1 months. Agreement rates of chemotherapy rates among omental and ovarian biopsies were moderate (CRS 1 22.9% vs 37.5% respectively, CRS 2 37.5% vs 35.4% and CRS 3 33.3% vs 16.7%). Progression free survival rates gradually declined among patients with omental CRS 3 and those with CRS 1 (18.7 vs 14 vs 10.3 months respectively, p=.003 ). Similar results were observed for overall survival rates, however, the results were not statistically significant (42.3 vs 32 vs 29.3 months respectively, p=.182 ). Conclusion: Evaluation of the chemotherapy response score from omental biopsies is an accurate predictor of survival rates of ovarian cancer patients undergoing interval debulking surgery, irrespective of the use of maintenance therapy. Further studies are needed to support our findings.